GR24-mediated enhancement of salt tolerance and roles of H2O2 and Ca2+ in regulating this enhancement in cucumber - Zhang, Xiao-Hua (Journal of plant physiology, 2022)
Copyright © 2022 Elsevier GmbH. All rights reserved.